2005
DOI: 10.1097/01.ogx.0000189144.21245.4c
|View full text |Cite
|
Sign up to set email alerts
|

A Sonographic Assessment of Different Patterns of Placenta Previa ???Migration??? in the Third Trimester of Pregnancy

Abstract: Preeclampsia has been associated with an increased risk of cardiovascular disease and also with a lowered risk of breast cancer later in life. These associations may represent underlying metabolic changes. The investigators undertook a case-control study in which metabolic profiles were examined in women who completed their pregnancies at age 30 and older and had no serious chronic disorders. Thirteen women had experienced preeclampsia in their first pregnancies, whereas 13 others had no complications. Preecla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…In contrast, those placentas previa that yielded a placental distance from the internal cervical os of more than 3.0 cm at final examination had a mean rate of migration of 4.1 mm/wk. A slower rate of placental migration was directly related to a lesser placental distance from the internal cervical os [8,[13][14][15]. These findings are similar to those of a previous report in which the mean rates of placental migration were 0.3 and 5.4 mm/ wk for those patients who had CD versus normal vaginal delivery, respectively [5,7,[9][10].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In contrast, those placentas previa that yielded a placental distance from the internal cervical os of more than 3.0 cm at final examination had a mean rate of migration of 4.1 mm/wk. A slower rate of placental migration was directly related to a lesser placental distance from the internal cervical os [8,[13][14][15]. These findings are similar to those of a previous report in which the mean rates of placental migration were 0.3 and 5.4 mm/ wk for those patients who had CD versus normal vaginal delivery, respectively [5,7,[9][10].…”
Section: Discussionsupporting
confidence: 82%
“…The location of the placenta and proximity of the placental edge to the internal cervical os was evaluated as a standard TVUS examination during the third trimester [8][9][10]. We regarded a placenta located within 30 mm of the internal os after 30 weeks' gestation as low-lying [6].Cases with a low-lying placenta were tagged prospectively during performance of the examination, and were subsequently reviewed for this study.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…1 It is also now clear that changes in placental location occur throughout gestation and are consequent to two phenomena, formation of the lower uterine segment and placental trophotropism. 11,15,16 Trophotropism is the term used to describe preferential proliferation of trophoblastic villi in regions of better endometrial supply along with atrophy of villi in areas with a poorer blood supply. 15,16 Placental position and shape can, therefore, change as pregnancy progresses.…”
Section: Placenta Previamentioning
confidence: 99%
“…11,15,16 Trophotropism is the term used to describe preferential proliferation of trophoblastic villi in regions of better endometrial supply along with atrophy of villi in areas with a poorer blood supply. 15,16 Placental position and shape can, therefore, change as pregnancy progresses. Trophotropism explains resolution of placenta previa, increase in pathologic extent of placenta previa, the development of succenturiate lobes or a bilobed placenta, odd-shaped placentas and abnormal cord insertions.…”
Section: Placenta Previamentioning
confidence: 99%
“…This is usually evaluated by transabdominal examination of the cervix and lower uterine segment with the bladder moderately full; however, the bladder should not be so full as to artificially elongate the cervix. 27 When the placenta fully covers the cervix and is implanted on both the anterior and posterior walls of the lower-uterine segment, by an overlap of 915 mm as seen on the initial scan at 18 to 23 weeks, there is a high likelihood of resultant delivery by Caesarean section. 18 One study found that scanning at 20 to 23 weeks decreased the number of false positives 19 ; however, most practitioners perform the anatomic survey at 18 to 20 weeks to allow for counseling and additional testing as needed.…”
Section: Placenta Previamentioning
confidence: 99%